Impact of Emotional Intelligence on the Job Performance of Employee - Pant, Ishita; Yadav, Rakesh Kumar (International Research Journal of Management, IT & Social Sciences, 2016)
Emotional intelligence means understanding oneâs own feelings and able to handle those feelings without disturbing themselves. In the same way understanding what others feel and handling relationship effectively motivates one to complete job creatively and perform among their pears. Stress Management is a system that is aimed to reduce stress and/or facilitate the person to cope with stress related instances. This study uses both primary and secondary data. The primary data was collected through questionnaire which is depending on Liker scale. The study confined to the sample size of 100 employees from five software industries namely HP, LENOVO, DELL, HCL & SONY, etc.Â  Finally researcher finds the relationship between the stress management and emotional intelligence. The study is concluded with the suggestion that the Emotional intelligence has ability to quickly reduce stress in the various situations, so we can say that higher level of EI is positively correlated with effectiveness of stress management among software employees.